Nonarteritic Anterior Ischemic Optic Neuropathy After Cataract Surgery: A Systematic Review and Meta-Analysis. Issue 1 (23rd March 2023) - Shew, William; Wang, Michael T. M.; Danesh-Meyer, Helen V.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Nonarteritic anterior ischemic optic neuropathy (NAION) has been reported to occur after cataract surgery. It is not clearly established whether cataract surgery increases the risk of NAION over baseline. Evidence Acquisition: Medline, PubMed, Embase, and Cochrane Central registers were systematically searched for eligible studies reporting on postcataract surgery NAION (psNAION) within 1 year. All peer-reviewed publications with events n ≥ 10 were included. Pooled incidence and odds/hazard ratios and 95% confidence intervals (CIs) were extracted and calculated using random effect models for early and delayed psNAION. Time to event data were pooled for temporal analysis of psNAION events within the first year. This systematic review was registered (PROSPERO CRD42021274383). Results: Nine articles met the selection criteria with five studies suitable for meta-analysis. A total of 320 psNAION cases, 1, 307 spontaneous NAION (sNAION) cases, 1, 587, 691 cataract surgeries, and 1, 538, 897 noncataract surgery controls were included. Pooling of 63, 823 cataract surgeries and 161, 643 controls showed a hazard ratio of 4.6 (95% CI 2.7–7.8) of psNAION within 1 year of surgery. Pooled unadjusted incidence of psNAION within 2 months was 99.92 (95% CI 38.64–161.19) per 100, 000/year, psNAION within 1 year was 32.36 (95% CI 9.38–55.34) per 100, 000/year, and sNAION was 8.87 (95% CI 2.12–15.62) per 100, 000/year. psNAION cases were older by a mean of 7.6 years; otherwise, pooled odds ratios for baseline risk factors in psNAION vs. sNAION cases were not statistically significant. psNAION within the first year peaked within 72 hrs and at 6 weeks after the surgery with 73% of cases occurring within 6 months. Conclusion: The risk of NAION after cataract surgery is four times greater within the first year and usually occurs within 6 months. However, the absolute risk remains low at 1 in 1, 000–3, 100 surgeries and is unlikely to warrant extra mention for consenting.